Utilitarian Shopping Value and Hedonic Shopping Value Influencing Repurchase Intention Mediated by Satisfaction - Purnama, Mardiah; Mugiono, Mugiono; Rofiq, Ainur (Green Publisher Indonesia, 2024)
This research aims to explain and analyze the factors that influence Repurchase Intention in e-commerce in 5 big cities in Indonesia. This research is also intended to explain the Satisfaction variable that can mediate Utilitarian Shopping Value and Hedonic Shopping Value on repurchase intention. The subjects of this research are Indonesian consumers who shop online for fashion products in 5 cities, which are the cities with main source of ecommerce visitors. In this research, the Likert Scale was used as a research instrument measurement scale to determine the opinions of consumers in 5 city in Indonesia regarding the following three factors: (1) hedonic shopping value is necessary for e commerce in order to encourage users to make a repeat purchase/repurchase intent; (2) Utillitarian shopping value has a positive and significant effect on Repurchase intention; (3) Satisfactory shopping value perceived adventure journey in shopping, for example, to get value added in getting promos or discounts there can lead users to repeat purchases; and (4) Utilian shopping value can increase satisfaction; (5) satisfaction mediates the relationship between the two variables; (6) satisfaction is still able to have a significant influence on the motivation shopping value (Utiliarian and hedonitic) on epurchase intention, even though the nature of the satisfaction variable is partial mediation.